Discussion on "Effect of soil spatial variability on failure mechanisms and undrained capacities of strip foundations under uniaxial loading". (February 2022) - Luo, Zhe
Abstract: It is a widely accepted practice to use finer meshes at soil domains of stronger interest and coarser meshes at other domains of less interest on a finite element model (FEM) to simultaneously save computational resources and achieve accuracy. But when the random field modeling is implemented into FEM consisting of unequal element sizes, the local averaging of soil property across the elements needs to be consistently applied on elements of various sizes. The mesh-dependent variance reduction factors are required in the statistics of a random field. Otherwise, the generated random field will not be stationary as desired, and the actual statistics of soil property mapped onto the FEM mesh will no longer be constant.